"Prefacing the Script" as an ethical response to state-mandated abortion counseling. Issue 1 (2nd January 2016) - Buchbinder, Mara; Lassiter, Dragana; Mercier, Rebecca; Bryant, Amy; Lyerly, Anne Drapkin
Abstract: Background : Laws governing abortion provision are proliferating throughout the United States, yet little is known about how these laws affect providers. We investigated the experiences of abortion providers in North Carolina practicing under the 2011 Woman's Right to Know Act, which mandates that women receive counseling with specific, state-prescribed information at least 24 hours prior to an abortion. We focus here on a subset of the data to examine one strategy by which providers worked to minimize moral conflicts generated by the counseling procedure. Drawing on Erving Goffman's work on language and social interaction, we highlight how providers communicated moral objections and layered meanings through a practice that we call prefacing the script .Methods : We conducted semistructured interviews with 31 physicians, nurses, physician assistants, and clinic managers who provide abortion care in North Carolina. Audio-recorded interviews were transcribed verbatim and analyzed using an inductive, iterative analytic approach, which included reading for context, interpretive memo-writing, and focused coding.Results: Roughly half of the participants (14/31) reported that they or the clinicians who performed the counseling in their institution routinely prefaced the counseling script with qualifiers, disclaimers, and apologies that clarified their relationship to the state-mandated content. We identified three performative functions of this practice: (1) enacting a frame shift from a medical to a legal interaction; (2) distancing the speaker from the authorial voice of the counseling script; and (3) creating emotional alignment.Conclusions : Prefacing state-mandated abortion counseling scripts constitutes a practical strategy providers use to balance the obligation to comply with state law with personal and professional responsibilities to provide tailored care, provide emotional support, and serve the patient's best interests. Our findings suggest that language constitutes a powerful resource for navigating and minimizing moral conflicts in health care.